Changes in serum levels of Total protein , Albumin and Globulin in patients with Behcet's Disease. - Al-Joofy K. Ikbal; Muslih K. Raad; Mousawy M. Khalida (College of Pharmacy / Mustansiriyah University, 2005)
In order to have an idea about some of biochemical changes which might play a role in the pathogenesis of Behcet's disease. Estimation of serum total protein, albumin, globulin and HLA typing were carried out in 70 patients with Behcets disease using colorematric, mathematic & microlymphocytotoxicity tests respectively, compared with 35 patients with recurrent oral ulcers, and 35 healthy control group. Hyperproteinemia, hyperglobulinemia with hypoalbuminemia were observed in those patients in comparison to control groups